Kajian Teknis Pengaruh Fragmentasi Hasil Peledakan di PT. Semen Padang - Muhammad Ridho; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. In mining activities with hard rock characteristics, it is necessary to do a blasting which aims to clean the rock, so that it can facilitate digging. The size of fragmentation as a result of blasting will affect to the digging time, the greater of the fragmentation that results will be the longer the time needed to digging the blasting material. Blasting geometry applied by PT. Semen Padang produces fragmentation measuring 53,86 cm with digging time of 14,29 seconds. In this study Blasting Geometry was used with ICI-explosive and RL. Ash theories. Where the fragmentation produced by the ICI-Explosive Theory is 47,86 cm with the digging time of 11,15 seconds, and with the Theory of RL. Ash fragmentation obtained is 43.71 cm with digging time of 8,6 seconds. Of the two theories, the theory of RL. Ash is better because it produces better fragmentation.Keywords: Blasting Geometry, Fragmentation, Digging Time, Kuz-Ram, Regression Analysis